2001
DOI: 10.1177/026988110101500108
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT1A receptor in schizophrenia: a promising target for novel atypical neuroleptics?

Abstract: Increasing attention is being directed towards the role of the serotonergic system in the neurochemistry of schizophrenia and antipsychotic drug treatment. This review considers the 5-HT1A receptor in this context. In patients with schizophrenia, the majority of post-mortem studies have reported increases in 5-HT1A receptor density in the prefrontal cortex in the approximate range 15-80%. Although the pathophysiological significance of this finding is unclear, given the location of a major proportion of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
133
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(144 citation statements)
references
References 87 publications
3
133
1
6
Order By: Relevance
“…Thus, the present data suggest that in this apomorphine-induced gating deficits model, a narrow window of efficacy exists between DA D 2 receptor blockade and serotonin 5-HT 1A receptor activation. While the latter property is considered to be desirable for attenuating negative, cognitive, and affective symptoms of schizophrenia, as well as neuroleptic-induced EPS (Millan, 2000;Bantick et al, 2001;Kleven et al, 2005), it appears that too pronounced an activation of 5-HT 1A receptors impairs the ability of compounds, such as SLV313 and SSR181507 to reverse apomorphine-induced PPI deficits. Taken together, these data indicate that 5-HT 1A activation can alter the antipsychotic-like effects of DA D 2 receptor antagonists in this model of positive symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present data suggest that in this apomorphine-induced gating deficits model, a narrow window of efficacy exists between DA D 2 receptor blockade and serotonin 5-HT 1A receptor activation. While the latter property is considered to be desirable for attenuating negative, cognitive, and affective symptoms of schizophrenia, as well as neuroleptic-induced EPS (Millan, 2000;Bantick et al, 2001;Kleven et al, 2005), it appears that too pronounced an activation of 5-HT 1A receptors impairs the ability of compounds, such as SLV313 and SSR181507 to reverse apomorphine-induced PPI deficits. Taken together, these data indicate that 5-HT 1A activation can alter the antipsychotic-like effects of DA D 2 receptor antagonists in this model of positive symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, most atypical antipsychotics are DA D 2 and 5-HT 2 receptors blockers, and it has been proposed that antagonist activity at 5-HT 2 receptors prevents the deleterious effects of DA D 2 receptor blockade, that is, extrapyramidal signs (EPS) (Kapur, 1996;Remington and Kapur, 1999). Besides, there is ample preclinical evidence that activation of 5-HT 1A receptors should also prove beneficial in schizophrenia (Millan, 2000;Bantick et al, 2001;Ichikawa et al, 2001). Hence, it has been repeatedly shown that 5-HT 1A receptor agonists prevent catalepsy (an animal model of EPS) produced by blockade of DA D 2 receptors (Wadenberg and Ahlenius, 1991;Wadenberg et al, 1994;Neal-Beliveau et al, 1993;Prinssen et al, 1998Prinssen et al, , 1999Depoortere et al, 2003;Kleven et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The present study focused on the interaction of estrogen with central serotonin-1A (5-HT 1A ) receptor function. Evidence for the importance of 5-HT 1A receptors in schizophrenia includes post-mortem research (Burnet et al, 1997;Simpson et al, 1996) and some atypical antipsychotics having high affinity for 5-HT 1A receptors (Bantick et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is an inhibitory G-protein coupled receptor that is located both presynaptically, as autoreceptors in the raphe nuclei, and postsynaptically, as heteroreceptors at highest density in the hippocampus and neocortex. In depression, reductions in 5-HT 1A receptor density have been found in a number of cortical regions using [ 11 C]WAY-100635 PET imaging (Drevets et al, 2000;Sargent et al, 2000), while in schizophrenia increases in receptor density have been found in prefrontal cortical regions using post-mortem techniques (reviewed in Bantick et al, 2001) although not with PET (Lombardo et al, 2002;Tauscher et al, 2002;Bantick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is of interest because 5-HT 1A agonists reduce neuroleptic-induced catalepsy and increase dopamine release in the frontal cortex in animals. In schizophrenia, they may therefore have efficacy against neurolepticinduced extrapyramidal side effects, negative symptoms, and perhaps cognitive impairment (reviewed in Bantick et al, 2001;Millan, 2000;Sharma and Shapiro, 1996). A drug's in vitro affinity for a receptor can be translated into adequate in vivo brain receptor occupancy if it has favorable absorption, metabolism, and passage across the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%